2022
DOI: 10.3390/su14148888
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impact on the Habitat Suitability of Pseudotsuga menziesii Mirb. Franco in Mexico: An Approach for Its Conservation

Abstract: One of the conifers that survived after the last glaciation is the Pseudotsuga menziesii (Mirb.) Franco. Due to the gradual increase in temperature, this species was forced to move from the south to the north and to higher elevation, causing a fragmented and intermittent distribution in Mexico. The main objective of this study was to model and identify suitable areas for the future conservation of the P. menziesii in Mexico. The specific objectives of this research were: (i) to model the habitat suitability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, these kinds of studies are very limited in Mexico, and the few that have been developed are focused on conifers under their natural distribution [39,63], and which occur in natural protected areas [43,69]. To conserve candelilla populations in the primary harvest areas in Mexico, this study has identified areas that may represent ideal conditions for the subsistence of the species in the context of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…However, these kinds of studies are very limited in Mexico, and the few that have been developed are focused on conifers under their natural distribution [39,63], and which occur in natural protected areas [43,69]. To conserve candelilla populations in the primary harvest areas in Mexico, this study has identified areas that may represent ideal conditions for the subsistence of the species in the context of climate change.…”
Section: Discussionmentioning
confidence: 99%